DIAGNOSTICS OF NON-RHEUMATIC CARDITIS IN CHILDREN - Aralov M. D.; Egamov K. H. (Web of Journals Publishing, 2025)
Heart muscle lesions are most often of non-rheumatic etiology, the main causes may be viral infections rather than bacterial ones. Research by N.A. Belokon et al. showed that in children, non-rheumatic carditis (NRC) can be congenital or acquired [1-8].
Keywords: Non-rheumatic carditis, children, etiology, viral infections, bacterial infections, diagnostics.